Aplikasi Pembelajaran Interaktif untuk Mata Pelajaran Tematik Kelas Satu di Sdit Al-Kautsar Cikarang Berbasis Multimedia - Hendry Janto; Nuraini Purwandari (UNIVERSITAS KALBIS, 2022)
Al-Kautsar SDIT School is an Integrated Islamic Elementary School in Cikarang, the teaching and learning system at this school still does not apply information technology. The school uses thematic textbooks for learning. The book combines many subjects into one entity in a printed book. The obstacles felt by the teacher were the lack of creativity in running a learning strategy for class I students. Students feel bored quickly if there is no interesting thing, so that pupils are difficult to pay attention and focus on while learning. Therefore, this research aims to combine the learning process with multimedia technology. By creating interactive learning applications for class I thematic subjects in SDIT Al-Kautsar Cikarang based multimedia. The method used in this research is Multimedia Development Life Cycle (MDLC) consisting of 6 phases: concept, design, material collecting, assembly, testing, and distribution. The result of this research is the finished result of interactive learning application for class I thematic subjects in SDIT Al-Kautsar Cikarang based multimedia, which contains learning material from thematic Book 1, there are text, images, audio, and video needed to support teaching and learning process in the application.